The Influences of Climatic and Lithological Factors on Weathering of Sediments in Humid Badland Areas - Xie, Chunxia; Antić, Nevena; Nadal-Romero, Estela; Yan, Luobin; Tosti, Tomislav; Djogo Mračević, Svetlana; Tu, Xinjun; Kašanin-Grubin, Milica (Frontiers in Earth Science, 2022)
Climate variables including temperature, rainfall intensity, rainfall acidity, and lithological properties are among the most important factors affecting rock weathering. However, the relative contribution of these four factors on rock weathering, especially on chemical weathering, is still unclear. In this study, we carried out a series of weathering-leaching rainfall simulations on four types of badland sediments under controlled conditions of two levels of temperature, rainfall intensity, and rainfall acidity based on the real field data from representative weather scenarios. The main objectives are 1) to explore the progressive change of sample surface and leachate characteristics and 2) to reveal the independent effects of temperature, rainfall intensity, rainfall acidity, and lithology and their relative contribution as well, on both mechanical and chemical weathering. Qualitative analysis on crack development and fragmentation of sample surface and quantitative analysis on the leachate volume, pH, electrical conductivity, and total cation and anion releases of sample leachate together demonstrated that for the investigated sediments, under the conditions of temperature, intensity, and acidity of rain that can be achieved in nature, high drying temperature obviously increases mechanical disintegration by promoting the rate and magnitude of moisture variations (wetting–drying alterations), while high rainfall intensity and acid rain have no obvious effect. Impact and importance of the drying process caused by high temperature between wetting events need more attention, rather than high rainfall intensity. Low temperature, high rainfall intensity, and acid rain contributing more hydrogen ions required for cation exchanges, rock type with more soluble minerals, all promote chemical weathering, and the influence of climatic and lithological factors on chemical weathering decreases in the following order: mineral composition> rainfall intensity > temperature > rainfall acidity. Climatic variations on temperature can modify weathering processes and in that way conditioned hydro-geomorphological processes in badland areas. Such changes should be considered for direct and indirect implications on badland dynamics.